(untitled) (International Seven Journal of Multidisciplinary, 2026)
Three-dimensional printing (3D printing) is one of the key technologies of Industry 4.0, with increasingly diversified applications and significant impact on strategic sectors such as education, healthcare, engineering, sustainability, art. This article presents a systematic review of scientific literature published between 2020 and 2024, aiming to identify the main application areas of 3D printing and analyze the methodological and thematic contributions of the selected studies. The search was conducted in the Web of Science (WoS) database, using descriptors in Portuguese, English, and Spanish related to technology and its applications. After the screening and selection process, 26 articles were included in the qualitative analysis. Thematic categorization allowed for the organization of studies into seven main areas: education, engineering/industry, biomaterials/biofabrication, human health, veterinary health, energy/sustainability, and art and design. The results show a balanced distribution across fields, with emphasis on educational and industrial applications. The analysis was complemented by a comparative table and a word cloud, reinforcing the versatility and interdisciplinary nature of the technology. The evidence highlights the potential of 3D printing as an educational, technological, and socially transformative tool, especially when aligned with sustainable and accessible practices. This study contributes to understanding the strategic role of 3D printing in Industry 4.0, highlighting trends, gaps, and research opportunities aligned with the Sustainable Development Goals of the 2030 Agenda.